Unlocking the Potential Value of BIM Implementation in Malaysia: A Pilot Study - Afifuddin Husairi, Hussain; Mohd Khairi, Abu Husain; Adi Irfan, Che Ani; Noor Irza, Mohd Zaki; Mohd Ali, Z. (EJAET, 2015)

(untitled)
Previous research has consistently shown that the implementation of BIM has brought tremendous benefits to clients. A number of countries around the world especially among the developed nations have realized the vast opportunities that BIM brings and have thus been investing to develop their own capability. In Malaysia, BIM is still in the infancy stage as it currently stands. As such, the implementation of BIM is likely to face a number of challenges in its adoption. Therefore, the aim of this research is to measure the potential of value of BIM implementation from the perspective of client organisation. A 25-item questionnaire was piloted and randomly distributed to 500 private clients organisations in Malaysia, which yielded 13% response rate. Rasch measurement model was employed in the analysis of responses from 65 clients’ organisations using WINSTEPS version 3.73. Preliminary results showed that clients’ organisations were divided into five groups according to separation strata namely: innovators (n=2); late adopters (n=9); early majority (n=23); late majority (n=9); and laggards (n=7). The most competent group had logit score of Pmax = +6.17 while the logit score for the least competent group, Pmin = -6.00. Preliminary findings suggest that Malaysia is on the right track to implement BIM like in other developed countries.